The Impact of Gamification on Motivation and Retention in Language Learning: An Experimental Study Using a Gamified Language Learning Application - P. Kamalesh, Kumar; C., Vairavan (INTI International University, 2024)
This study investigates the effects of gamification elements such as points, levels, and badges on motivation and retention in language learning. An experimental design was employed, observing two groups of learners over a 10-week period. One group engaged with a gamified version of a language learning app, while the control group used the app without these features. Key variables, including time spent on the app, lesson progression, and motivation levels, were analysed through surveys and usage data. Results indicated a significant increase in both motivation and retention within the gamified group, providing empirical support for integrating game mechanics into language learning.